tDCS over the left prefrontal Cortex improves mental flexibility and inhibition in geriatric inpatients with symptoms of depression or anxiety: A pilot randomized controlled trial - Mathieu Figeys; Mathieu Figeys; Sheryn Villarey; Ada W. S. Leung; Ada W. S. Leung; Jim Raso; Steven Buchan; Hubert Kammerer; David Rawani; David Rawani; Megan Kohls-Wiebe; Esther S. Kim; et al. (Frontiers Media S.A., 2022)
BackgroundPatients with depression and/or anxiety are commonly seen in inpatient geriatric settings. Both disorders are associated with an increased risk of cognitive impairments, notably in executive functioning. Transcranial direct current stimulation (tDCS), a type of non-invasive brain stimulation, involves the administration of a low-dose electrical current to induce neuromodulation, which ultimately may act on downstream cognitive processing.ObjectiveThe purpose of this study was to determine the effects of tDCS on executive functioning in geriatric inpatients with symptoms of depression and/or anxiety.DesignPilot Randomized Controlled Trial.SettingSpecialized geriatric wards in a tertiary rehabilitation hospital.MethodsThirty older-aged adults were recruited, of which twenty completed ten-to-fifteen sessions of 1.5 mA anodal or sham tDCS over the left dorsolateral prefrontal cortex. Cognitive assessments were administered at baseline and following the tDCS protocol; analyses examined the effects of tDCS on cognitive performance between groups (anodal or sham tDCS).ResultstDCS was found to increase inhibitory processing and cognitive flexibility in the anodal tDCS group, with significant changes on the Stroop test and Trail Making Test-Part B. No significant changes were observed on measures of attention or working memory.DiscussionThese results provide preliminary evidence that tDCS-induced neuromodulation may selectively improve cognitive processing in older adults with symptoms of depression and/or anxiety.Clinical Trials Registrationwww.clinicaltrials.gov, NCT04558177